Diverse angle-length-width model for 3D/4D/5D steel fiber reinforced concrete under tension. (10th January 2021) - Gao, Danying; Ding, Chong; Pang, Yuyang; Yang, Lin; Huang, Yunchao; Tang, Jiyu
Graphical abstract: Highlights: An analytical DAM for the tensile stress-crack width constitutive was proposed. Effects of initial and residual embedded lengths of fiber on DAM were analyzed. The integral region of the pullout force was divided by using the polar coordinate. The DAM proposed was applicable to SFRC members with 3D, 4D, and 5D steel fibers. Abstract: The most important characteristic of steel fiber reinforced concrete (SFRC) is its excellent post-cracking behavior. An analytical diverse angle-length-width model (DAM) was proposed to calculate the tensile stress-crack width ( σ-w ) constitutive behavior of SFRC members subjected to tension and to evaluate its post-cracking behavior. In the proposed model, the tensile stress in SFRC members with end-hooked steel fibers was generated from the straight fiber part, the end-hooked fiber part, and the concrete part. The effects of straight and end-hooked parts were separately considered, and three cases for different crack width ranges were analyzed for each part. The model was derived by considering all of the possible fiber inclination angles, fiber embedded lengths, and crack widths. It was found that SFRC members with new types of 4D and 5D steel fibers possessed a higher tensile stress than those with 3D steel fibers, and the tensile stress intensity increased with the increasing fiber volume fraction. Finally, the accuracy of the model was verified by comparing the values by DAM with the experimental results based on the sectional analysis.